How zoledronic acid improves osteoporosis by acting on osteoclasts - Wang, Biao; Zhan, Yi; Yan, Liang; Hao, Dingjun (Frontiers in Pharmacology, 2022)
Osteoporosis is called a silent disease, because it is difficult to detect until comprehensive examinations for osteoporosis are performed or osteoporotic fractures occur. Zoledronic acid is currently the first-line anti-osteoporotic drug, with good efficacy and treatment compliance. A major advantage of zoledronic acid is that intravenous zoledronic acid often guarantees a therapeutic effect for up to 1 year after infusion. The reasons why zoledronic acid is effective in improving osteoporosis are that it can inhibit osteoclast differentiation and induce osteoclast apoptosis, thus suppressing bone resorption and increasing bone density. The story between zoledronic acid and osteoclasts has been written long time ago. Both the canonical receptor activator of the receptor activator of nuclear factor-κB ligand (RANKL) pathway and the non-canonical Wnt pathway are the main pathways by which zoledronic acid inhibits osteoclast differentiation. Farnesyl pyrophosphate synthase (FPPS), reactive oxygen species (ROS), and ferroptosis that was first proposed in 2012, are all considered to be closely associated with zoledronic acid-induced osteoclast apoptosis. Here, we provide a brief review of the recent progress on the study of zoledronic acid and osteoclasts, and hope to elaborate how zoledronic acid improves osteoporosis by acting on osteoclasts.